Pengaruh Efikasi Diri Dan Kecerdasan Emosional Terhadap Kemandirian Belajar Ekonomi Siswa Kelas XI IPS SMA Negeri 1 Siantar T.A 2022/ 2023 Dengan Motivasi Berprestasi Sebagai Variabel Intervening - Cah Dayani Saragih; Putri Kemala Dewi Lubis (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This study aims to determine the Effect of Self-Efficacy and Emotional Intelligence on the Independence in Learning Economics of Class XI Social Sciences Students of SMA Negeri 1 Siantar Academic Year 2022/2023 with Achievement Motivation as an Intervening Variable. This type of research is ex post facto research. The population in this study were all students of class XI IPS SMA Negeri 1 Siantar, totaling 128 students. The sample used in this study amounted to 97 students who were taken based on simple random sampling technique. Data collection techniques were carried out by observation, interviews, and questionnaires. Then the classic assumption test in this study is the normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing was carried out by linear regression analysis for hypotheses 1, 2, 3, 4 and 5, path analysis and Sobel test for hypotheses 6 and 7 through the SPSS.25 program. The research results show that: (1) There is a positive and significant influence between self-efficacy on student achievement motivation with tcount(2.461) > ttable(1.661) and sig. of 0.016 <0.05. (2) There is a positive and sig. between emotional intelligence on student achievement motivation with tcount(7.111) > ttable(1.661) and sig. of 0.000 <0.05. (3) There is a positive and significant influence between self-efficacy on student learning independence with tcount(2.135) > ttable(1.661) and sig. of 0.035 <0.05. (4) There is a positive and significant influence between emotional intelligence on student learning independence tcount(3.967) > ttable(1.661) and sig. of 0.000 <0.05. (5) There is a positive and significant influence of achievement motivation on student learning independence with a value of tcount(9.369) > ttable(1.661) with a sig. 0.000 < 0.05. (6) Achievement motivation is able to mediate the influence of self-efficacy on student learning independence with a Sobel test statistic score of 2.427 > 1.96 (5% level) and a one-tailed probability value of 0.007 <0.05. (7) achievement motivation is able to mediate the effect of emotional intelligence on student learning independence, with a Sobel test statistic score of 5.925 > 1.96 (5% level) and a one-tailed probability value of 0.0 <0.05.